2012
DOI: 10.1371/journal.pone.0033460
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Bias in Decision-Making under Risk: Evaluating the Perception of Reward, Its Probability and Value

Abstract: BackgroundThere are few clinical tools that assess decision-making under risk. Tests that characterize sensitivity and bias in decisions between prospects varying in magnitude and probability of gain may provide insights in conditions with anomalous reward-related behaviour.ObjectiveWe designed a simple test of how subjects integrate information about the magnitude and the probability of reward, which can determine discriminative thresholds and choice bias in decisions under risk.Design/MethodsTwenty subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 57 publications
3
26
0
Order By: Relevance
“…We determined whether: (1) higher vs. lower magnitude predictable money reinforcement would decrease cocaine choice; and (2) probabilistic and predictable money reinforcement conditions equated for overall expected value would differentially alter cocaine choice. We predicted that fewer cocaine choices would be made with (1) higher vs. lower magnitude predictable money alternative, consistent with prior findings on the effect of non-drug magnitude on cocaine choice (Higgins et al, 1994a; Donny et al, 2003, 2004); and (2) higher vs. lower probability money reinforcement, consistent with findings that human subjects exhibit a predictability bias (Sharp et al, 2012). …”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…We determined whether: (1) higher vs. lower magnitude predictable money reinforcement would decrease cocaine choice; and (2) probabilistic and predictable money reinforcement conditions equated for overall expected value would differentially alter cocaine choice. We predicted that fewer cocaine choices would be made with (1) higher vs. lower magnitude predictable money alternative, consistent with prior findings on the effect of non-drug magnitude on cocaine choice (Higgins et al, 1994a; Donny et al, 2003, 2004); and (2) higher vs. lower probability money reinforcement, consistent with findings that human subjects exhibit a predictability bias (Sharp et al, 2012). …”
Section: Introductionsupporting
confidence: 81%
“…Given that humans exhibit a predictability bias (Sharp et al, 2012) and that probability discounting is routinely observed in animals and human subjects (Green et al, 2010; Mobini et al, 2002; Rachlin et al, 1991), this was unanticipated. Several factors may explain this result.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded one patient who performed poorer than 60% correct on catch trials (exclusion criteria from Sharp et al, 2012). Four patients and four controls did not show any deviation from responding by selecting the prospect with a higher probability of gain in every trial (Prospect 1).…”
Section: Resultsmentioning
confidence: 99%
“…1) and in Sharp et al (2012), we hypothesized that these deviations could be captured by taking into account variations in sensitivity to probability and magnitude. Alternate models separating out these effects of probability and magnitude were fitted (see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation